The impact of social comparison, FoMo, cyberbullying, and social media addiction on social anxiety among Malaysian youth - Kunhao, Zhang; Ma’rof, Aini Azeqa; Dahamat Azam, Mohamad Naqiuddin (Human Resource Management Academic Research Society, 2024)
This study explores the relationship between social comparison, Fear of Missing Out (FoMO), cyberbullying, social media addiction, and social anxiety among Malaysian youth. The research examines how these key dimensions—social comparison, FoMO, cyberbullying, and social media addiction—impact social anxiety levels. A sample of 432 Malaysian youths was analyzed using quantitative methods, including correlation and regression analyses. The results reveal that social media addiction is the strongest predictor of social anxiety, followed by FoMO, social comparison, and cyberbullying. Higher levels of social media addiction were significantly associated with increased social anxiety, while the presence of FoMO and frequent social comparison further exacerbated this anxiety. Cyberbullying also contributed to elevated social anxiety levels. These findings underscore the urgent need for responsible social media use, awareness programs, and interventions targeting online behaviors to mitigate social anxiety among youth. The study provides valuable insights into the complex interplay between these factors and offers practical recommendations for reducing social anxiety in the digital age.